Viruses Demonstrate Selective Survival During Simulated Anaerobic Digestion of Plant Biomass - Shevchenko, O.V.; Kharina, A.V.; Snihur, H.O.; Shevchenko, T.P.; Budzanivska, I.H.; Шевченко, О.В.; Харіна, А.В.; Снігур, Г.О.; Шевченко, Т.П.; Будзанівська, І.Г. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
Objective. This research aimed at laboratory simulation of anaerobic digestion of plant biomass contaminated by a mixture of viruses with a wide host range to evaluate if viruses can retain their infectivity and pose a biohazard during the use of plant-based reusable resources such as digestate. Methods. Anaerobic digestion was simulated in air-tight desiccators using anaerobic bags and indicator strips to ensure proper conditions, and using fresh biomass of naturallyvirus-infected plants. In one of the variants, a commercial mixture of anaerobic bacteria and enzymes was also added to see if it would be more efficient in terms of plant digestion and virus inactivation. For serological detection of the tomato mosaic virus, cucumber mosaic virus, and potato virus Y, DAS-ELISA was used with commercial diagnostic kits and positive controls. Absorbance values were measured at 405 nm. Total RNA was extracted using a RNeasy Plant Mini kit following the manufacturer’s instructions. Molecular detection of viruses was carried out by two-step RT-PCR using specific oligonucleotide primers available from the literature. To check if the viruses can retain their infectivity after the anaerobic digestion of plant biomass waste, a bioassay was used where Nicotiana rustica plants producing necrotic lesions upon infection with many viruses were mechanically inoculated at the stage of 2 true leaves. For statistical processing of data, the mean and standard error were calculated using Microsoft Excel software. Results. After prolonged anaerobic digestion, tomato mosaic virus was still detected in plant residues, but it is important to note that it was also found in high concentration in the liquid phase. Hence, during the anaerobic digestion, a significant proportion of the virus was successfully eluted from plant residues into the digestate. Interestingly and contrary to tomato mosaic virus, cucumber mosaic virus has not practically eluted to the liquid phase. On the other hand, potato virus Y was supposedly completely decomposed during the anaerobic digestion of plant biomass waste, as it was not detected either by ELISA or by PCR. It is likely that not all of the investigated viruses represent a potential biohazard in the context of the use of renewable resources. RT-PCR outcomes showed the presence of tomato mosaic virus and cucumber mosaic virus both in the solid and the liquid phases, augmenting the ELISA data. Lastly, bioassay results have confirmed that at least tomato mosaic tobamovirus may escape the aggressive process of waste decomposition and remain able to infect host plants raising issues about the safety of reusable plant resources. Conclusions. The survival of plant viruses during plant biomass waste processing was studied in the context of biological safety. The preservation of serological markers and genetic signatures of model viruses in the process of anaerobic digestion has been confirmed. For the first time, it was proven that tomato mosaic virus may preserve its infectivity during long-term incubation of plant biomass waste in anaerobic conditions, which requires further attention when using renewable resources. On the example of PVY, it has been shown that potyviruses do not survive during anaerobic digestion and therefore may not pose an epidemic risk in using processed renewable resources. It has been demonstrated that artificial introduction of anaerobic microorganisms does not have a decisive effect on the stability of the studied model viruses.